PEMETAAN SEJARAH FILM DI INDONESIA: STUDI LITERATUR RISET SEJARAH FILM DI NDONESIA - Lukas Sarungu (Universitas Slamet Riyadi, 2022)
The history of Indonesian Film only gains little attention from Indonesian scholars, until now there are no handbooks and textbooks that can guide researchers and communication historians to understand this field. This illustrates that Indonesian film history is still an under-researched field. This study seeks to mapped references on the history of Indonesian cinema. The method used is library research. Sources of data are from the National Library, Jakarta; National Press Monument, Surakarta; and the Garba Rujukan Digital (Garuda) portal from Ristekbrin. The data shows that the mapping of film history can be divided into 3 genres, namely, government policies and film censorship in Indonesia, the history of film development, and biographies of film people.